Prevalence of Anaemia in Sri Lanka - Mudalige, R.; Nestel, P. (My University, 1996)
Haemoglobin (Hb) measurements were included in the Third National Nutrition and Health Survey, conducted between October 1994 and January 1995 by the Ministry of Policy Planning, Ethnic Affairs and National Integration, in order to obtain nationally representative data on the prevalence of anaemia in Sri Lanka. Finger prick samples of blood were placed immediately in a HemoCue (photometer) cuvette and the Hb reading recorded. A Hb concentration below 11, g/dL among children below 60 mo and among pregnant women was taken as an indication of anaemia. For children 5 yr and older and nonpregnant women the cut-off point was 12 g/dL, and 11 g/dl- for pregnant women. For children between 3 and 59 mo, the Hb concentration was 11.0 g/dl- (S.D 1,.5 g/ dL),11.6 (S.D 1.3) g/ dL for children 5 to 10.9 yr, 12.3 (S.D Lq g/dL for children between 11 and 18.9 yr and 12.0 (S.D 1.5) g/dL for non pregnant mothers. The mean FIb concentration varied by province, the lowest levels being in the North Western Province and highest in the Uva Province. A sectoral difference was seen among non-pregnant women only, being significantly lower in the estate sector than in the rural and urban sectors. Anaemia prevalence was 45"h among pre-school children,58% among children between 5 and 10.9 y, 36o/" among adolescents. -{mong women, 45% of non-pregnant and 39o/o of pregnant women were anaemic. TWo percent of children 6-11., 1.2-'1.7 and 24-35 mo were -\rerely anaemic (FIb below 7 g/ dL) and 1% of preg-nant women were very severely anaemic lHb less than 4 g/dl.). The results indicate that several groups in the population could benefit from interventions, including iron supplements and food fortification.